Ricinodendron heudelotii (Euphorbiaceae) seed oil prevents DMBA-induced breast cancer under menopause-like conditions in Wistar rats - Zingué, Stéphane; Tchoupang, Edwige Nana; Madji, Linda Takou; Pehuie Fomat, Boris Hugor; Mafogang, Borelle; Njamen, Dieudonné; Mendimi, Joseph Marie Nkodo (Frontiers in Pharmacology, 2024)
Despite efforts, breast cancer remains associated with a high incidence and mortality rate. Ricinodendron heudelotii also known as “Njansang,” is a plant used for cancer treatment. While several reports on the anticancer potential of its leaves exist, little is known about its seed oil. This study aimed to evaluate the in vitro and in vivo anti-breast cancer activity of “Njansang” seed oil. The inhibitory effect of “Njansang” seed oil was determined using MTT and CCK-8 dye reduction assays. Breast cancer was induced with DMBA and promoted with E2V (1 mg/kg) for 4 weeks in ovariectomized rats (menopausal condition). Evaluated parameters included tumor incidence, tumor mass and volume, histopathology, breast cancer biomarker CA 15–3, antioxidant status (CAT, GSH, MDA, NO, SOD), TNF-α and INFγ levels, lipid profile (total cholesterol, LDL-cholesterol, triglycerides and HDL-cholesterol), as well as toxicity parameters (ALT, AST, creatinine). “Njansang” oil significantly reduced the growth of ER+ (MCF-7) and triple negative (MDA-MB 231) adenocarcinoma cells in vitro as well as tumor incidence, tumor mass and CA 15–3 levels in vivo. It exhibited antioxidant activity, characterized by an increase in SOD and catalase activities, GSH levels and decreased MDA levels compared to the DMBA group. TNF-α and INF-γ levels were reduced following oil treatment, while total cholesterol, LDL-cholesterol and triglyceride levels were reduced. The aforementioned findings confirm the protective effects of “Njansang” oil on induced breast cancer in ovariectomized rats.